2021
DOI: 10.1111/apt.16404
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ginger as antiemetic in children with acute gastroenteritis: a randomised controlled trial

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
0
9
1
4
Order By: Relevance
“…They observed that both ginger and ondansetron reduced the frequency of vomiting; however, ginger was more effective than ondansetron. In this line, Nocerino et al 31 studied through a double-blind, randomized placebo-controlled trial the use of a preparation containing 47.4% (w/w) of ginger for the reduction of vomiting associated with acute gastroenteritis (AGE) in children; they found that the ginger preparation was effective in reducing vomiting in children with AGE. Also, Menon et al 32 in a clinical trial with 10 patients, compared the effectiveness of ibuprofen and dried ginger powder as alternative medicines for the management of pain and gingival inflammation following periodontal surgery; they observed no difference between ibuprofen and ginger in the reduction of pain and gingival inflammation.…”
Section: Overview Of the Investigated Clinical Trials And The Main Outcomes Of Ginger Bioactive Compoundsmentioning
confidence: 99%
“…They observed that both ginger and ondansetron reduced the frequency of vomiting; however, ginger was more effective than ondansetron. In this line, Nocerino et al 31 studied through a double-blind, randomized placebo-controlled trial the use of a preparation containing 47.4% (w/w) of ginger for the reduction of vomiting associated with acute gastroenteritis (AGE) in children; they found that the ginger preparation was effective in reducing vomiting in children with AGE. Also, Menon et al 32 in a clinical trial with 10 patients, compared the effectiveness of ibuprofen and dried ginger powder as alternative medicines for the management of pain and gingival inflammation following periodontal surgery; they observed no difference between ibuprofen and ginger in the reduction of pain and gingival inflammation.…”
Section: Overview Of the Investigated Clinical Trials And The Main Outcomes Of Ginger Bioactive Compoundsmentioning
confidence: 99%
“…The use of ginger as an antiemetic is well-known in China and is used in traditional Chinese medicine, where ginger is rich in curcumin, curcumin, gingerols, and curcuminoids ( Ahmed et al, 2021 ). These active substances influence gastrointestinal motility and promote gastric emptying, while they affect the central nervous system by mediating the 5-hydroxytryptamine-3 of 5-hydroxytryptamine (5-HT), reducing nausea and vomiting ( Nocerino et al, 2021 ). Marx et al (2017) conducted a double-blind randomized intervention with ginger in 51 patients, identifying less fatigue in the intervention group ( p = 0.006) from the three chemotherapy cycles, especially in the third cycle.…”
Section: Mitigation Of Adverse Drug Reactions To Parpi By Phytochemicalsmentioning
confidence: 99%
“…A total of 33% of patients treated with ginger had resolution of vomiting after the first dose, compared to 13% in the placebo arm ( p = 0.003). The ginger product used was a liquid containing 10 mg of ginger extract per 20 drops (1% ginger by weight), given at a dose of 10 mg every 8 h until the resolution of vomiting [ 58 ].…”
Section: Gingermentioning
confidence: 99%